Efficiency of Modular Bridge Configurations: A Study on the Structural Stability and Capacity of Single- and Double-Story Modular Bridges - Mohamed Embaby; M. Hesham El Naggar (Buildings)
This study investigates the structural performance and load-bearing capacity of single- and double-story modular bridge configurations using both experimental testing and finite element analysis. A full-scale field test was conducted on a 45.7 m double-story bridge subjected to truck loading at ten distinct positions along the span. Midspan deflections and axial strains of key members were measured and analyzed at each loading position to assess the bridge’s response under service loads. The experimental data were used to validate three-dimensional finite element (FE) models and refine modeling techniques for the double-story modular bridge. The validated FE models enabled further analysis of the structural performance of double-truss–double-story (DD) and quadruple-truss–single-story (QS) modular bridge configurations, both in single- and double-lane setups. The numerical results demonstrated that the double-story configuration with double truss lines per side provided a notable improvement in stiffness and load-carrying capacity compared to the single-story configuration with quadruple truss lines. Moreover, single-lane bridges exhibited better performance than their double-lane equivalents, emphasizing the impact of bridge width on structural stability. Wider, double-lane bridges were found to be more prone to out-of-plane buckling at midspan, with the top chords experiencing significantly greater deformation. Buckling analyses indicated that, although the DD and QS configurations had comparable critical loads, their failure mechanisms differed. Finally, live load factors predicted through the models were compared with the requirements of the Canadian Highway Bridge Design Code (CHBDC), confirming that the DD configuration in a two-lane setup meets code expectations and demonstrates effective structural performance.